2020
DOI: 10.1371/journal.pone.0231881
|View full text |Cite
|
Sign up to set email alerts
|

Weirdo19ES is a novel singleton mycobacteriophage that selects for glycolipid deficient phage-resistant M. smegmatis mutants

Abstract: The sequencing and bioinformatics analysis of bacteriophages infecting mycobacteria has yielded a large amount of information on their evolution, including that on their environmental propagation on other genera such as Gordonia, closely related to Mycobacterium. However, little is known on mycobacteriophages cell biology such as the nature of their receptor (s) or their replication cycle. As part of our ongoing screening for novel mycobacteriophages, we herein report the isolation and genome bioinformatics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Although phage DCp1 had a lytic effect on host strain D22, successive passages on the medium showed that phage-resistant mutants still appeared. Based on previous studies, we speculated that phage DCp1 produced phage-resistant mutants at a frequency of about 10 −6 –10 −7 [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although phage DCp1 had a lytic effect on host strain D22, successive passages on the medium showed that phage-resistant mutants still appeared. Based on previous studies, we speculated that phage DCp1 produced phage-resistant mutants at a frequency of about 10 −6 –10 −7 [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each cluster is composed of phage which shares a minimum of 35% of their genes and members of subclusters share 90% (Pope et al, 2017;Hatfull, 2018). MP which does not meet the minimum sequence homology required for inclusion in a cluster is termed 'singletons' (Suarez et al, 2020). For a comprehensive review of the MP clusters and genomics, please see Hatfull et al (Hatfull, 2022).…”
Section: Mycobacteriophagementioning
confidence: 99%
“…It has been reported that MSMEG_0392 encodes a glycosyltransferase, which can affect the synthesis of M. smegmatis cell wall glycopeptidolipids 38 and plays a key role in M. smegmatis resistance to phage I3 39 and phage Weirdo19ES. 40 Therefore, we designed primers to amplify MSMEG_0392 and sent the amplified product to BGI for sequencing. The results showed that MSMEG_0392 gene amplified fragment using M12 genome as a template had an Adenine insertion mutation at position 817 (Figure 7).…”
Section: M12 Resistance To Swu1 Did Not Correlate With the Inactivation Of Msmeg_3705mentioning
confidence: 99%